Action inhibition and affordances associated with a non-target object: An integrative review. (May 2020) - Vainio, L.; Ellis, R.
Highlights: Evidence shows that response activation triggered by affordances of a non-target are automatically inhibited. The article highlights the special neural processes that differentiate these affordance distractor effects from other distractor effects. The article proposes that the prefrontal processes exaggerate inhibition of response activation triggered by affordances of a non-target. Abstract: This article reviews evidence for the special inhibitory mechanisms required to keep response activation related to affordances of a non-target object from evoking responses. This evidence presents that response activation triggered by affordances of a non-target are automatically inhibited resulting, for example, in decelerated response speed when the response is compatible with the affordance. The article also highlights the neural processes that differentiate these non-target-related affordance effects from other non-target-related effects such as the Eriksen flanker effect that―contrary to these affordance effects―present decelerated response speed when there is incompatibility between the non-target and the response. The article discusses the role of frontal executive mechanisms in controlling action planning processes in these non-target-related affordance effects. It is also proposed that overlapping inhibition mechanisms prevent executing impulsive actions relative to affordances of a target and exaggerate inhibition of response activation triggered by affordances of a non-target.